Internet-Portal Of Organizational-Methodical Providing Distancionnikh Olympiads On Programirovaniyu (Journal of Information Technologies in Education (ITE), 2009)
In the article the internet-portal of the organizational-methodical providing of the controlled from distance olympiads is described on programming, his use in an educational process on employments on programming, fakul'tativakh on preparation of the gifted young people to the olympiad on programming.
Keywords: automated verification of decisions; e-olimp; internet-portal; olympiad from programming; sporting programming